Cross-cultural pragmatics of refusal to invitation among Malays and Germans - Mohd Jalis, Farhana Muslim; Abdul Jabar, Mohd Azidan; Abdul Halim, Hazlina; Bukhardt, Jürgen Martin (Persatuan Linguistik Malaysia, 2020)
This present study on cross-cultural pragmatics aims to investigate the pragmatic behaviours through the refusal speech act uttered by the Malay and German native speakers when receiving invitations from different levels of interlocutors. In this particular study, 15 native speakers of Malay and 15 native speakers of German were asked to refuse invitations made by an interlocutor. The study employed methodology from the combination of the refusal taxonomies proposed by Beebe et al., (1990) and Al-Issa (2003). The data was then collected via a Discourse Completion Test (DCT). The results showed that both Malays and Germans used several similar strategies when refusing invitations; however, both cultures also exhibited differences in term of the type and frequency of refusal strategies employed in each situation. This study is esteemed to not only contribute to the widened corpus of cross-cultured refusal behaviour’s literature, yet it is also counted to the literature on pragmatic behaviour specifically between Malays and Germans’ language and culture.